Persistent decrease of renal functional reserve in patients after cardiac surgery-associated acute kidney injury despite clinical recovery. Issue 2 (19th July 2018) - Husain-Syed, Faeq; Ferrari, Fiorenza; Sharma, Aashish; Hinna Danesi, Tommaso; Bezerra, Pércia; Lopez-Giacoman, Salvador; Samoni, Sara; de Cal, Massimo; Corradi, Valentina; Virzì, Grazia Maria; De Rosa, Silvia; Muciño Bermejo, María Jimena; et al.
Abstract: Background: Cardiac surgery is a leading cause of acute kidney injury (AKI). Such AKI patients may develop progressive chronic kidney disease (CKD). Others, who appear to have sustained no permanent loss of function (normal serum creatinine), may still lose renal functional reserve (RFR). Methods: We extended the follow-up in the observational 'Preoperative RFR Predicts Risk of AKI after Cardiac Surgery' study from hospital discharge to 3 months after surgery for 86 (78.2%) patients with normal baseline estimated glomerular filtration rate (eGFR), and re-measured RFR with a high oral protein load. The primary study endpoint was change in RFR. Study registration at clinicaltrials.gov Identifier: NCT03092947, ISRCTN Registry: ISRCTN16109759. Results: At 3 months, three patients developed new CKD. All remaining patients continued to have a normal eGFR (93.3 ± 15.1 mL/min/1.73 m 2 ). However, when stratified by post-operative AKI and cell cycle arrest (CCA) biomarkers, AKI patients displayed a significant decrease in RFR {from 14.4 [interquartile range (IQR) 9.5 − 24.3] to 9.1 (IQR 7.1 − 12.5) mL/min/1.73 m 2 ; P < 0.001} and patients without AKI but with positive post-operative CCA biomarkers also experienced a similar decrease of RFR [from 26.7 (IQR 22.9 − 31.5) to 19.7 (IQR 15.8 − 22.8) mL/min/1.73 m 2 ; P < 0.001]. In contrast, patients with neither clinical AKI nor positive biomarkers had no such decrease of RFR. Finally, of the three patients who developed new CKD, two sustained AKI and one had positive CCA biomarkers but without AKI. Conclusions: Among elective cardiac surgery patients, AKI or elevated post-operative CCA biomarkers were associated with decreased RFR at 3 months despite normalization of serum creatinine. Larger prospective studies to validate the use of RFR to assess renal recovery in combination with biochemical biomarkers are warranted.